1999
DOI: 10.1093/jn/129.12.2170
|View full text |Cite
|
Sign up to set email alerts
|

Some Dietary Fibers Reduce the Absorption of Carotenoids in Women

Abstract: Dietary fiber may be partly responsible for the lower bioavailability of carotenoids from food than from purified supplements. Due to the lack of detailed information available, we investigated the effects of different kinds of dietary fiber on the absorption of carotenoids and alpha-tocopherol. Six healthy young women received an antioxidant mixture consisting of beta-carotene, lycopene, lutein, canthaxanthin and alpha-tocopherol together with a standard meal. The meal did not contain additional dietary fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
151
1
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(167 citation statements)
references
References 42 publications
9
151
1
6
Order By: Relevance
“…Moreover, differences in bioavailability could distort any direct relationship between intakes and intestinal absorption. For example, b-carotenoid, but not a-tocopherol, absorption is reduced by some dietary fibres (Riedl et al, 1999).…”
Section: Dietary Antioxidants In Diabetes Mellitusmentioning
confidence: 99%
“…Moreover, differences in bioavailability could distort any direct relationship between intakes and intestinal absorption. For example, b-carotenoid, but not a-tocopherol, absorption is reduced by some dietary fibres (Riedl et al, 1999).…”
Section: Dietary Antioxidants In Diabetes Mellitusmentioning
confidence: 99%
“…Fibers also increase intestinal content, viscosity and volume thereby slowing processes of diffusion of micelles on the absorbent surface of enterocytes (Yonekura & Nagao, 2007;Eroglu & Harrison, 2013). Besides, Riedl et al (1999) confirmed that dietary fibers decrease carotenoids absorption in human. Differences in carotenoids bioavailability observed in our study could be explained by dietary fibers content of studied meals.…”
Section: Discussionmentioning
confidence: 66%
“…Nature and distribution of dietary fibers in the meals could also explain the difference in bioavailability. In fact, Riedl et al (1999) reported that effect of dietary fibers on carotenoids absorption varies according to the type of fiber.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are insufficient data to firmly draw conclusions about this matter. Most likely, the effect of the fibre depends on the type of mineral or vitamin, the intestinal transit time and the degree of bacterial fibre degradation in the gut (64,80,81) . The combination therapy with soluble fibre and statins may also have some safety limits, while unfavourable reductions in HDL-cholesterol have been described and in one study reduced statin absorption from the gut was suggested after a high intake of soluble fibre (74) .…”
Section: Safety Aspects Of Combination Therapy With Soluble Dietary Fmentioning
confidence: 99%